UAVs for Vegetation Monitoring - de Castro Megías, Ana; Shi, Yeyin; Peña, Jose M.; Maja, Joe (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book compiles a set of original and innovative papers included in the Special Issue on UAVs for vegetation monitoring, which proves the wide scope of UAVs in very diverse vegetation applications, both in agricultural and forestry scenarios, ranging from the characterization of relevant vegetation features to the detection of plant or crop stressors. New methods and techniques are developed and applied to diverse vegetation scenarios to meet the main challenge of sustainability.